2021
DOI: 10.3847/psj/abe1c3
|View full text |Cite
|
Sign up to set email alerts
|

Will the Mars Helicopter Induce Local Martian Atmospheric Breakdown?

Abstract: Any rotorcraft on Mars will fly in a low-pressure and dusty environment. It is well known that helicopters on Earth become highly charged due, in part, to triboelectric effects when flying in sandy conditions. We consider the possibility that the Mars Helicopter Scout (MHS), called Ingenuity, flying at Mars as part of the Mars 2020 Perseverance mission, will also become charged due to grain-rotor triboelectric interactions. Given the low Martian atmospheric pressure of ∼5 Torr, the tribocharge on the blade cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Our experiments may provide a basis to estimate electric charges on Martian sands, e.g., in terrains where electrostatics may be a problem for landers on Mars (Farrell et al 2021). Furthermore, these insights will be useful to improve models of sand transport on the Martian surface and to predict wind conditions necessary for aeolian geomorphodynamics on Mars (Parteli & Herrmann 2007;Pähtz et al 2014;Lämmel et al 2018).…”
Section: Discussion and Application To Marsmentioning
confidence: 90%
“…Our experiments may provide a basis to estimate electric charges on Martian sands, e.g., in terrains where electrostatics may be a problem for landers on Mars (Farrell et al 2021). Furthermore, these insights will be useful to improve models of sand transport on the Martian surface and to predict wind conditions necessary for aeolian geomorphodynamics on Mars (Parteli & Herrmann 2007;Pähtz et al 2014;Lämmel et al 2018).…”
Section: Discussion and Application To Marsmentioning
confidence: 90%
“…Recently, Farrell et al. (2021) have suggested that the rotors of the Ingenuity helicopter could cause localized breakdown during takeoff or landing. While Ingenuity does not have the instrumentation to make such measurements electronically, videography in low‐light conditions could reveal such processes.…”
Section: Discussionmentioning
confidence: 99%
“…We conclude this paper by highlighting several current and upcoming missions that may provide exciting insights into electrical processes on Mars and Titan. Recently, Farrell et al (2021) have suggested that the rotors of the Ingenuity helicopter could cause localized breakdown during takeoff or landing. While Ingenuity does not have the instrumentation to make such measurements electronically, videography in low-light conditions could reveal such processes.…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 99%
“…Beyond the importance of dust lifting in general on Mars, the specific problem of dust mobilization by rotor downwash is of interest in aviation—in terrestrial helicopter operations, the effect is termed “brownout” (analogous to “whiteout” in snow). In addition to possible degradation of optical sensor performance, lofted dust might cause triboelectric charging (e.g., Farrel et al., 2021 ; Lorenz, 2020 ). With helicopters now being considered for sample return operations at Mars, and the development of the Dragonfly rotorcraft for Titan underway, the possibility of extraterrestrial brownout means in situ measurements at Mars have considerable value in testing the generality of brownout models (e.g., Rabinovitch et al., 2021 ) under physical conditions quite different from Earth.…”
Section: Introductionmentioning
confidence: 99%